Modified Kantorovich-Stancu operators (II) - GAVREA, Ioan; OPRIȘ, Adonia-Augustina (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
In this paper, we introduce a new kind of Bernstein-Kantorovich- Stancu operators. These operators generalize the operators introduced in the paper [2] by V. Gupta, G. Tachev and A.M. Acu. Mathematics Subject Classification (2010): 41A25, 41A36.